A resolução de problemas como uma proposta de ensino de análise combinatória - Bassani, Jheimys Bezerra (2019)
This dissertation aims to address ways that facilitate the teaching and learning of combinatorial analysis through a problem-solving approach, pursuing broad and se quential solutions. It starts with the intuitive idea of counting, which will then be com plemented by the fundamental principle of addition and multiplication. After that, the concepts of simple, circular permutation will be presented, together with repeated ele ments and chaotic. We also address simple and complete combination, and Kaplansky’s lemmas by studying the main problems of combination. The problems proposed in the chapters were selected in order to complement the theoretical part- commonly omitted- and to demonstrate alternative resolution techniques, such as counting by inclusion exclusion and recurrence, always oriented to the pursuit of solutions that promote logical thinking and not the use of formulas